304 DOUBLE-BLINDED RANDOMIZED STUDY OF TEMPORARY GASTRIC ELECTRICAL STIMULATION: PRELIMINARY RESULTS OF THE ENDOSTIM STUDY (ENDOSCOPIC STIMULATION TEMPORARILY IMPLANTED MUCOSALLY). Issue 1 (1st January 2007) - Thompson, J.; Johnson, W. D.; Minocha, A.; Abell, T. L.
Abstract : Introduction: Permanently implanted gastric electrical stimulation (GES) has been shown to be a successful therapy for many aspects of gastroparesis (GP). Recently, endoscopic temporary GES (GIE, 2005), has been advocated as a method to rapidly determine the possible beneficial effects of this therapy. However, temporary GES (Temp GES) has not been studied in a blinded manner. Patients: We studied 58 patients (11 males, 47 females, mean age 46 years) with the symptoms of GP and an underlying diagnosis (idiopathic [ID], n = 38; diabetes mellitus (DM), n = 13; postsurgical [PS], n = 7) in a randomized placebo-controlled crossover study of temp GES as two consecutive 4-day sessions. Methods: After baseline assessments of symptoms (including vomiting) and health-related quality of life (HRQOL), patients underwent endoscopic placement of Temp GES on day 1 and then had devices turned ON/OFF through day 4, when another assessment was done. Patients were crossed over to OFF/ON days 5 through day 8 when final assessments were performed. Results were compared by t -tests within and between groups and reported as mean ± SE. Results: Twenty-eight patients had ON-OFF and 30 patients had OFF-ON; 45 of 58 patients finished all 8 days. When analyzed for all patients ON versus all patients OFF, both vomiting frequency and HRQOL improved significantly ( p < .05). When analyzed for the first session, the results were even more significant: the mean number of days vomiting decreased from 1.4 OFF to 0.4 ON ( p = .001) and the mean number of days with nausea deceased from 1.6 OFF to 0.8 ON ( p = .002). Conclusions: This blinded comparison of temporary endoscopic GES is the first evidence-based study of its effectiveness. Further stratification of results from the EndoSTIM study should provide additional information about which gastroparesis patients may benefit most from temporary GES.